Dermatosurgical rounds: shark island pedicle flap for skin defect of the alar crease area after basal cell carcinoma removal - Georgi Tchernev; Simona Kordeva (Dermatology Reports)
A 67-year-old female presented to the Dermatology Department with a tumor formation located on the left lateral side wall of the nose, measuring 1,5/1,2 cm in size, which had been slowly growing over the past few years. The tumor exhibited a shiny, pink-colored surface with a dome-shaped appearance, irregular borders, and superficial telangiectasias, raising clinical suspicion for basal cell carcinoma. Additionally, there was no reported history of skin cancer in any family member or painful sunburns during childhood. The patient was recommended surgical excision under local anesthesia for the suspected lesion.